THE QUEST FOR HAPPINESS IN WOLE SOYINKA’S THE TRIALS OF BROTHER JERO - Christine Osae (University of Kuningan, 2016)
In pursuit of happiness, humans have indulged in atrocious acts and lost the moral membrane, perhaps with a conviction that they can find fulfillment. Literature, being a mirror of the society, is the best medium to help in correction of these wrongs. This article is aimed at the analysis of the major fictional characters in Soyinka’s The Trials of Brother Jero to reveal their daily struggles in search of happiness. A textual analysis in relation to Aristotle’s doctrine of happiness leads to a conclusion that Soyinka has successfully created lifelike characters whose struggles in life are relatable yet unproductive as far as the quest for happiness is concerned.Keywords: virtue, golden mean, happiness, fulfillment